EVALUASI KEPUASAN PENGGUNAAN SISTEM PENERIMAAN MAHASISWA BARU (PMB) STIKES YRSDS MENGGUNAKAN METODE SERVQUAL - Paskalis Bayu Saputra; Een Kurniawati; Imam Mahdi; Kevin Jesaya; Dyan Angesti (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to evaluate user satisfaction with the New Student Admission (PMB) system at STIKES YRSDS using the SERVQUAL (Service Quality) method. SERVQUAL measures the gap between users’ expectations and perceptions of the PMB system’s services across five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This research uses a descriptive quantitative approach with 72 student respondents from the 2025/2026 academic year. Data were collected through a Likert-scale questionnaire and analyzed using SERVQUAL gap analysis. The results show that three SERVQUAL attributes have negative gap values, meaning users’ expectations have not been fully met. In the empathy dimension, attributes E3 and E4 have gap values of −0.04 and −0.06. Similarly, the reliability dimension shows a negative gap of −0.12. Overall, the level of user satisfaction with the STIKES YRSDS PMB system is good; however, improvements are still needed, especially in handling system errors and providing online customer complaint services.